Cyathea arjae Latiff (Cyatheaceae), a new Species of dwarf tree-fern from Sayap, Mt. Kinabalu, Sabah, Malaysia - Latiff, A. (Universiti Kebangsaan Malaysia, 2015)
A dwarf tree‑fern, Cyathea arjae Latiff is described as a new species from Sayap, Mt. Kinabalu, Sabah, Malaysia. This new species belongs to Schizocaena group which has basiscopic veins that originate from the costa and not from the costule. It is closely related to C. capitata in having simply pinnate fronds of which the apex is a deltoid lamina. Holttum’s key was modified.